Vennskap og ambivalens - Hylland, Ole Marius (Tidsskrift for kulturforskning, 2002)
This article deals with the relationship between an élite and the folk, as this relationship is visible in Norwegian popular enlightenment (folkeopplysning). In particular, the article explores the rhetorics of a Norwegian educational journal, entitled Folkevennen ("Friend of the people"). This journal (1852-1900) was dedicated to transforming the Norwegian folk - that is in essence the peasantry - into an enlightened, efficient and morally sound one. This was no easy task The goal of the popular educators can be described as the attempt to lessen the gap between the real and the ideal people. The ideal people was conscious of its historical heritage and of the value of time, while the real people could be considered historically ignorant and morally corrupt. The article tries to uncover what kind of ambivalence that was characteristic of this kind of educational philanthropism.